Single‐Molecule Magnetism, Enhanced Magnetocaloric Effect, and Toroidal Magnetic Moments in a Family of Ln4 Squares. Issue 44 (18th September 2015) - Das, Chinmoy; Vaidya, Shefali; Gupta, Tulika; Frost, Jamie M.; Righi, Mattia; Brechin, Euan K.; Affronte, Marco; Rajaraman, Gopalan; Shanmugam, Maheswaran
Abstract Three cationic [Ln4] squares (Ln=lanthanide) were isolated as single crystals and their structures solved as [Dy4(μ4‐OH)(HL)(H2L)3(H2O)4]Cl2⋅(CH3OH)4⋅(H2O)8 (1), [Tb4(μ4‐OH)(HL)(H2L)3(MeOH)4]Cl2⋅(CH3OH)4⋅(H2O)4 (2) and [Gd4(μ4‐OH)(HL)(H2L)3(H2O)2(MeOH)2]Br2⋅(CH3OH)4⋅(H2O)3 (3). The structures are described as hydroxo‐centered squares of lanthanide ions, with each edge of the square bridged by a doubly deprotonated H2L2− ligand. Alternating current magnetic susceptibility measurements show frequency‐dependent out‐of‐phase signals with two different thermally assisted relaxation processes for 1, whereas no maxima in χM" appears above 2.0 K for complex 2. For 1, the estimated effective energy barrier for these two relaxation processes is 29 and 100 K. Detailed ab initio studies reveal that complex 1 possesses a toroidal magnetic moment. The ab initio calculated anisotropies of the metal ions in complex 1 were employed to simulate the magnetic susceptibility by using the Lines model (POLY_ANISO) and this procedure yields J1=+0.01 and J2=−0.01 cm−1 for 1 as the two distinct exchange interactions between the DyIII ions. Similar parameters are also obtained for complex 1 (and 2) from specific heat measurements. A very weak antiferromagnetic super‐exchange interaction (J1=−0.043 cm−1 and g=1.99) is observed between the metal centers in 3. The magnetocaloric effect (MCE) was estimated by using field‐dependent magnetization and temperature‐dependent heat‐capacity measurements. An excellent agreement is found for the −ΔSm values extracted from these two measurements for all three complexes. As expected, 3 shows the largest −ΔSm variation (23 J Kg−1 K−1) among the three complexes. The negligible magnetic anisotropy of Gd indeed ensures near degeneracy in the (2S+1) ground state microstates, and the weak super‐exchange interaction facilitates dense population of low‐lying excited states, all of which are likely to contribute to the MCE, making complex 3 an attractive candidate for cryogenic refrigeration.